PENGUKURAN ATAS TINGKAT PENGUNGKAPAN SUKARELA DENGAN MENGGUNAKAN GRAPHICAL INFORMATION DISCLOSURE INDEX (GIDI) - MURTANTO; HELEN INDRAYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
This study examines empirically the extent of voluntary disclosure of 70 companies in Indonesia (divided into two categories, which are the participants of Annual Report Award – ARA and Non ARA) by using Graphical Information Disclosure Index (GIDI). The results show that generally, the level of voluntary disclosure still at poor level. But, specifically there were any differentiation in ARA category (level of voluntary disclosure reach average level) and non ARA category (level of voluntary disclosure still at poor level). Graphical information in Indonesian companies has a tendency to use bar chart with 5 years time series. The numbers of topics graphed varies widely while the most commonly graphed was net income (loss). The most commonly graphed of key financial variables was operating income (loss)